Guinea : Development Policy Review - World Bank (Washington, DC, 2012)
Following a decade of relatively strong growth, Guinea's economic performance weakened beginning in 2000. During 1992-1999, growth averaged 4.4 percent a year as the Government implemented a program of economic reforms aimed at liberalizing its economy and improving the environment for private sector investment. With a tightening of financial policies over the 1990s, inflation reached single digits by the late 1990s and the fiscal deficit averaged just over 3 percent of Gross Domestic Product (GDP) in the second half of the 1990s. However, since 2000 growth slowed to an average of 2.8 percent a year and inflation increased to 39 by 2006. Guinea's worsening economic performance since 2000 reflects a weaker policy framework and exogenous shocks. Macroeconomic policies were relaxed, as fiscal policy was loosened and monetary policy became highly accommodative. Government revenues from the mining sector dropped, despite a recovery in the price of bauxite-Guinea's most important export. Also, a heightened level of regional insecurity and a resulting considerable influx of refugees in Guinea put pressure on government expenditures. As a result, the fiscal deficit rose to an average of 5 percent of GDP in 2000-2004. An accommodative monetary policy led to double digit inflation and a crowding out of credit to the private sector. A concomitant slowdown in the implementation of economic reforms, coupled with increased uncertainty in the political climate and deteriorating quality of public institutions, contributed to the slowdown in economic activity.